Enhancement of photocatalytic decomposition of perfluorooctanoic acid on CeO2/In2O3. Issue 76 (29th July 2016) - Jiang, Fang; Zhao, Haitao; Chen, Huan; Xu, Chenmin; Chen, Jian
Abstract : The x CeO2 /In2 O3 catalysts were synthesized and used for photocatalytic decomposition of PFOA. The excellent activity and stability was derived from inhibition of electron-holes recombination caused by the charge transfer between CeO2 and In2 O3 . Abstract : CeO2 -doped indium oxide photocatalysts ( x CeO2 /In2 O3 ) with various CeO2 doping amounts were synthesized and systematically characterized by X-ray powder diffraction (XRD), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), UV-vis spectra, photoluminescence spectroscopy (PL) and photocurrent measurements. The as-obtained x CeO2 /In2 O3 photocatalysts were used in photocatalytic degradation of PFOA for the first time and much higher photocatalytic activity of x CeO2 /In2 O3 than CeO2 and In2 O3 was obtained under UV light irradiation. The excellent photocatalytic activity of 0.86% CeO2 /In2 O3 could be mainly derived from effective inhibition of recombination of photo-induced electron-holes caused by the charge transfer between CeO2 and In2 O3 . Moreover, the 0.86% CeO2 /In2 O3 catalyst showed excellent photocatalytic stability in cycling runs for the photocatalytic degradation of PFOA, providing a great potential of CeO2 /In2 O3 catalysts for PFOA treatment.